The impact of chloride desalination on the corrosion rate of archaeological iron. (October 2013) - Rimmer, Melanie; Watkinson, David; Wang, Quanyu
Abstract : Although desalination of archaeological iron reduces its chloride concentration and enhances object stability, the reduction in corrosion rate that this produces has never been quantified. This study measures post-treatment corrosion rates in accelerated corrosion environments to identify the impact of removing chloride ions on corrosion rate. Thirty-five archaeological iron nails, treated individually in either alkaline sulphite or nitrogen-deoxygenated sodium hydroxide, were exposed to 75°C and 75% relative humidity together with 31 untreated objects from the same archaeological sites. Object weight change and visual examination of physical change before and after the test period were used to monitor corrosion. 77% of treated objects showed no weight gain and no visible signs of corrosion, while 90% of untreated objects did corrode. The impact of chloride on corrosion of untreated objects was clearly established by a significant linear correlation between chloride content and weight gain. Treated objects with <400 ppm chloride content showed no corrosion behaviour. Corrosion of treated objects was attributed to incomplete treatment: 93% of objects treated to <5 mg/l Cl − in the final solution bath displayed no corrosion behaviour. Based on these results, desalination of iron objects to enhance their stability offers a valuable option for reducing corrosion rates of archaeological iron, which should increase object lifespan. The results also raise the question of whether low levels of post-treatment residual chloride produce corrosion of any significance. Answering this will be an important step forward for managing the preservation of archaeological iron.